Amputation of phenol using barium embedded and Ba-HDTMA modified power station solid waste: Column dynamics. Issue 4 (December 2016) - Shah, Bhavna A.; Patel, Hiren J.; Shah, Ajay V.
Graphical abstract: Abstract: The aim of the study was to examine the adsorption capability of barium embedded and Surfactant modified zeolitic materials, which were synthesized from power station solid waste by microwave assisted alkaline hydrothermal reflux method. Power station solid waste and modified synthesized materials were characterized by XRF, PXRD, SEM, FTIR, TGA and BET-BJH instrumental methods. Batch Studies were performed to explore the outcome of various parameters such as pH (1–12), contact time (0–360 min), Sorbent dose (0.2–10 g L −1 ), initial sorbate concentration (50–300 mg L −1 ) and temperature (30–60 °C). Uptake of ionisable compounds is dependent greatly on pH. Batch sorption experiments showed that efficiency of MZCFA (24.19 mg g −1 ) and SMZCFA (28.74 mg g −1 ) is raised as compared to CFA (10.48 mg g −1 ). Surface modification enhances phenol removal from aqueous solutions. Langmuir, Freundlich and Temkin isotherms have been studied, among them Langmuir isotherm is best suited. Pseudo-second-order was best fitted out of Pseudo-first-order, Pseudo-second-order and Intraparticle diffusion model for sorption kinetics. The breakthrough capacities acquired by column studies shows lower sorption capacity compare to batch studies. Regeneration studies were carried out using 0.5 M NaOH and HCl solutions. The modified zeolitic materials enhanced the sorption of phenol from aqueous solution.